2022
DOI: 10.1177/1358863x221130380
|View full text |Cite
|
Sign up to set email alerts
|

Livedoid vasculopathy: A review with focus on terminology and pathogenesis

Abstract: Livedoid vasculopathy (LV) is a rare thrombotic vasculopathy of the dermis characterized by painful, relapsing ulcers over the lower extremities. Diagnosis is challenging due to the overlap in clinical appearance and nomenclature with other skin disorders. Treatment selection is complicated by poor understanding of the pathogenesis of LV and lack of robust clinical trials evaluating therapy efficacy. The terminology and pathophysiology of LV are reviewed here, along with its epidemiology, clinical and histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…He was diagnosed as livedoid vasculopathy by his clinical appearance and the further confirmed the diagnosed by both skin biopsy and the recommended diagnostic pathway. 2 He experienced significant improvement in symptoms during the summer when he began taking a daily dose of 30 mg prednisone, which was later tapered to a maintenance dose of 10 mg. Unfortunately, in summer, his condition deteriorated, and prednisone therapy at 30 mg had a minimal impact.…”
Section: Case Presentationsmentioning
confidence: 99%
See 1 more Smart Citation
“…He was diagnosed as livedoid vasculopathy by his clinical appearance and the further confirmed the diagnosed by both skin biopsy and the recommended diagnostic pathway. 2 He experienced significant improvement in symptoms during the summer when he began taking a daily dose of 30 mg prednisone, which was later tapered to a maintenance dose of 10 mg. Unfortunately, in summer, his condition deteriorated, and prednisone therapy at 30 mg had a minimal impact.…”
Section: Case Presentationsmentioning
confidence: 99%
“… 1 Microscopically, it is marked by focal microvascular thrombosis within the lumina without a significant inflammatory infiltrate. 2 However, the pathogenesis of LV remains unclear. Recent studies have revealed hypercoagulability, encompassing microcirculatory and thrombotic events, with an inflammatory mechanism having a supporting role.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of LV consists of pain management, wound care, medicines that address the blood clots that cause the ulcers, and medicines that suppress the immune system (Table 1). 6,7 Treatment often requires collaboration among different medical specialties, such as dermatologists, wound care specialists, hematologists, rheumatologists, vascular medicine specialists, and/or vascular surgeons.…”
Section: How Is LV Treated?mentioning
confidence: 99%
“…A clinical diagnosis of LV was defined by having ≥2 characteristic clinical findings including livedo reticularis or racemosa, ulceration on the distal legs or atrophie blanche. 4 Clinical examination findings and laboratory results were reviewed to determine whether patients had venous insufficiency or hypercoagulabilityassociated LV. Age of symptom onset was defined by the onset of cutaneous signs of disease, most commonly purpuric patches, livedo reticularis or racemosa and retiform purpura.…”
mentioning
confidence: 99%